Mengkaji Hubungan Hakikat Manusia Dan Pendidikan - M. Yunus Abu Bakar; Ahmad Zidqy Azmy Hilmani; Zulfa Kalimatul Fajriyyah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Education is a complex process, which includes more than just imparting knowledge, but also includes the formation of human values. Philosophy, as the foundation of educational science, has a crucial role in guiding and influencing the process of forming these values. Educational philosophy provides guidance and direction in developing educational theories into meaningful educational science, as well as assisting in setting educational goals that are based on solid values